KONSEP BIOPHILIC DALAM PERANCANGAN ARSITEKTUR - Ronald Justice (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2021)
Abstract: Various attempts were made to reconnect humans with the buildings and places they inhabit. Biophilic design, as the newest theory of reconnection, essentially incorporates organic life into the built environment. This study aims to explore the biophilic concept in architectural design as a literacy reference in the field of architecture. The research method is through literature review and interviews with the primary data source of an architect and one other architect as a secondary data source. The collected data were analyzed using the Biophilia Architecture theory by Prof. Samalavicius (2020). The analysis showed that the primary source was not included in the Biophilia category, while the secondary data sources had applied the Biophilia concept. The study based on the Biophilic Architecture theory concludes that the concept of biophilic design is an architectural approach to solving residential needs problems by bringing the natural atmosphere into space as a therapy for its occupants both psychologically and physiologically. Meanwhile, understanding the creativity of an architect's work can be done through Intangible (intangible) and Tangible (real). The architectural design process consists of the analysis stage, the synthesis stage, and the evaluation stage, which are known as the divergent, transformation, and convergent stages.Abstrak: Berbagai upaya dilakukan untuk menghubungkan kembali manusia dengan bangunan dan tempat yang mereka huni. Desain biofilik sebagai teori rekoneksi terbaru, menggabungkan kehidupan organik ke dalam lingkungan binaan secara esensial. Penelitian ini bertujuan menggali konsep biophilic dalam perancangan arsitektur sebagai referensi literasi dalam bidang arsitektur. Metode penelitian melalui kajian literatur dan interview sumber data primer seorang arsitek dan satu orang arsitek lainnya sebagai sumber data sekunder. Data yang terkumpul dianalisis menggunakan teori Biophilia Architecture oleh Prof. Samalavicius (2020). Hasil analisa menunjukkan sumber primer belum termasuk kategori Biophilia, sedangkan sumber data sekunder telah menerapkan konsep Biophilia. Pengkajian berdasarkan teori Biophilic Architecture disimpulkan bahwa konsep parancangan biophilic merupakan pendekatan arsitek untuk memecahkan permasalahan kebutuhan hunian dengan membawa suasana alam kedalam ruang sebagai terapi bagi penghuninya baik psikologis maupun fisiologis. Sedangkan memahami kreativitas karya arsitek dapat dilakukan melalui Intangible (tak berwujud) dan Tangible(nyata). Proses perancangan arsitektur terdiri dari tahapan analisis, tahap sintesis, dan tahap evaluasi yang dikenal dengan tahap divergen, transformasi, dan konvergen.